Rare case of circumferential esophageal peeling - Kentaro Tominaga; Atsunori Tsuchiya; Hiroki Sato; Yui Ishii; Nobutaka Takeda; Kazuki Natsui; Yuzo Kawata; Naruhiro Kimura; Yoshihisa Arao; Suguru Takeuchi; Kazunao Hayashi; Junji Yokoyama; et al. (Clinical Case Reports, 2020)
Abstract This report highlights the easy peeling of the esophageal epithelium with Nikolsky phenomenon after swallowing the foreign body and the healing status of the esophagus only 3 days later in a patient of pemphigus vulgaris.